Comparative study on thermal performance of MEPCM suspensions in parallel and divergent minichannel heat sinks. (May 2018) - Ho, C.J.; Chang, Po-Chieh; Yan, Wei-Mon; Amani, Mohammad
Abstract: In this work, the augmentation in the hydrothermal performance of parallel and divergent minichannel heat sinks (MCHSs) containing microencapsulated phase change material (MEPCM) suspensions is investigated. Accordingly, the effect of diverging minichannels with the angles of 1.38° and 2.06° on the pressure drop and heat transfer performance in the presence of 2%, 5%, and 10% MEPCM particles at different Reynolds numbers from 238 to 1375, under various different heat fluxes of 3.2 × 10 4, 4 × 10 4, and 4.8 × 10 4  W/m 2, with the inlet temperature of 34 ± 0.2 °C is evaluated. The results also compared with the corresponding data in a parallel MCHS. It was found that the implementation of MEPCM suspension yielded to the increase of both the heat transfer and pressure drop. Diverging the minichannels and incrementing its angle significantly reduced the pressure drop penalty, especially at higher Reynolds number and greater mass fractions. The heat transfer effectiveness was also increased by diverging the minichannels with the angle of 1.38°, especially for higher concentrations and higher heat fluxes. The increment of the divergence angle to 2.06° had a detrimental impact on the thermal performance of the suspension and decreased the heat transfer coefficients to even less that that in the parallel MCHS. The results reveal that diverging the minichannels can effectively intensify the contribution of MEPCM suspensions in heat sinks in a certain range of parameter combinations.